ANALISIS TEORITIK DAN KAJI EKSPERIMENTAL UNTUK MENENTUKAN KEKAKUAN STATIK DARI BANTALAN ROL - Ishak S Iskandar; Komang Bagiasna; Zainal Abidin (Mesin, 1997)
This paper describes theoretical and experimental study of the static bearing stiffness. This research is motivated by the role of bearing stiffness in determining the natural frequency of a rotor-shaft system. Previous investigators, White and Harris, have developed an analytical tool to calculate the bearing stiffness. However, this analytical results were not supported by experimental data. In this work, an experimental study was done in order to determine the static bearing stiffness. These experimental results are then compared to those obtained by White and Harris analysis. The analysis and experimental study will pave the way toward the determination of the dynamic bearing stiffness.